Poison flower [compact disc, unabridged] : a Jane Whitefield novel - Perry, Thomas, 1947- (Perry, Thomas, 1947- Jane Whitefield novel (Tantor Media), 2012)
In this exciting seventh entry in Thomas Perry's Jane Whitefield series, Jane spirits James Shelby, a man unjustly convicted of his wife's murder, out of the criminal court building in downtown Los Angeles--but the price of Shelby's freedom is high.